Lobbying and Innovation in the Financial Sector - Gustavson, Reid E.M. (Université d'Ottawa | University of Ottawa, 2013)
The financial collapse of 2008 can most easily be explained by poor regulation of the banking sector. Many scholars attribute this lack of regulation to the banking lobbyists’ contributions to influence the politicians for favourable policies. We utilize the theoretical framework established by Perez-Saez and Semenov (Working Paper, 2012), which develops the argument that greater contributions by bank lobbyists will result in greater financial instability and more risk. We empirically test this claim by doing a crosssectional regression of all 50 States. We use proxies for financial instability acting as the dependent variable, and proxies for lobbying influence as the independent variables. We find support for the claim. Our results consistently show a positive correlation between the amount the bank lobbyists spent, and the variability of the financial stability indicator.